PD‐L1 testing for lung cancer in the UK: recognizing the challenges for implementation. Issue 2 (30th June 2016) - Cree, Ian A; Booton, Richard; Cane, Paul; Gosney, John; Ibrahim, Merdol; Kerr, Keith; Lal, Rohit; Lewanski, Conrad; Navani, Neal; Nicholson, Andrew G; Nicolson, Marianne; Summers, Yvonne
Abstract : A new approach to the management of non‐small‐cell lung cancer (NSCLC) has recently emerged that works by manipulating the immune checkpoint controlled by programmed death receptor 1 (PD‐1) and its ligand programmed death ligand 1 (PD‐L1). Several drugs targeting PD‐1 (pembrolizumab and nivolumab) or PD‐L1 (atezolizumab, durvalumab, and avelumab) have been approved or are in the late stages of development. Inevitably, the introduction of these drugs will put pressure on healthcare systems, and there is a need to stratify patients to identify those who are most likely to benefit from such treatment. There is evidence that responsiveness to PD‐1 inhibitors may be predicted by expression of PD‐L1 on neoplastic cells. Hence, there is considerable interest in using PD‐L1 immunohistochemical staining to guide the use of PD‐1‐targeted treatments in patients with NSCLC. This article reviews the current knowledge about PD‐L1 testing, and identifies current research requirements. Key factors to consider include the source and timing of sample collection, pre‐analytical steps (sample tracking, fixation, tissue processing, sectioning, and tissue prioritization), analytical decisions (choice of biomarker assay/kit and automated staining platform, with verification of standardized assays or validation of laboratory‐devised techniques, internal and external quality assurance, and audit), and reporting and interpretation of the results. This review addresses the need for integration of PD‐L1 immunohistochemistry with other tests as part of locally agreed pathways and protocols. There remain areas of uncertainty, and guidance should be updated regularly as new information becomes available.